ANALISIS MANAJEMEN PELATIHAN DI RUMAH SAKIT - Ikhsan, Fairuz Zahra; Gunawan, Susilawati; Al Aufa, Badra; Supriadi, Supriadi; Aprilianti, Neni (Jurnal Keperawatan dan Kesehatan, 2024)
Training management is crucial to ensure that the training process runs smoothly and meets both organizational and employee goals. At Hermina Hospital Bogor, 22.5% of employees have not met the minimum required training hours. The training process faces challenges, including limited space, incomplete attendance, and scheduling issues. This study aimed to analyze the gaps in training at Hermina Hospital Bogor, using both quantitative and qualitative methods from March to May 2023. Qualitative data were gathered through interviews with three key informants, selected via purposive sampling, and observations of the training process. Quantitative data were obtained from implementation surveys and pre-post tests for the Isolation Awareness training, involving 31 participants. Qualitative analysis used content analysis, while the Wilcoxon test was applied for quantitative data. The training process includes needs assessment, planning, implementation, and evaluation. Training needs are identified through gap analysis, covering issues raised in morning meetings, unit evaluation results, and proposals from stakeholders, competencies performance gaps. Implementation challenges include rescheduling and participant absence. Online training faces additional barriers, such as a lack of computers and poor internet connectivity. Improvements in training management can be achieved by developing training facilities, enhancing online tools and e-learning modules, and increasing participant involvement through the Documentation System application.